Ionic Liquid–Stabilized Titania Quantum Dots Applied in Adhesive Resin. (June 2019) - Garcia, I.M.; Souza, V.S.; Hellriegel, C.; Scholten, J.D.; Collares, F.M.
Quantum dots (QDs; 1 to 10 nm) were recently synthesized by sol-gel and used as nonagglomerated nanoparticles in adhesive resin. The sol-gel process presented a low yield and resulted in a liquid product without stability. In this study, an imidazolium ionic liquid (IL; 1- n -butyl-3-methylimidazolium tetrafluoroborate, BMI.BF4) was used as stabilizing agent to synthesize titanium dioxide QDs (TiO2QDs/BMI.BF4) via a chemical route. The product was isolated as powder after washing, centrifuging, and drying. An experimental adhesive resin was formulated by mixing methacrylate monomers and a photoinitiator system. The TiO2QDs/BMI.BF4 powder was incorporated at 2.5 (G2.5% ) and 5 (G5% ) wt% in the adhesive resin, and one group remained without TiO2QDs/BMI.BF4 powder as the control (Gctrl). The TiO2QDs/BMI.BF4 powder was analyzed by micro-Raman spectroscopy, thermogravimetry, and transmission electron microscopy. The dispersion of TiO2QDs/BMI.BF4 powder was analyzed in the polymerized adhesive resin with transmission electron microscopy and fluorescence microscopy. The adhesive resins were evaluated for immediate and long-term antibacterial activity, cytotoxicity, polymerization behavior, degree of conversion, softening in solvent, immediate and long-term microtensile bond strength, and fracture pattern. The TiO2QDs/BMI.BF4 powder showed peaks of anatase and rutile and 26 wt% of BMI.BF4 . TiO2QDs/BMI.BF4 presented a minimum size of 1.19 nm, a maximum size of 7.11 nm, and a mean ± SD size of 3.54 ± 1.08 nm. TiO2QDs/BMI.BF4 was dispersed in the adhesive resin without agglomeration, presenting intermittent luminescence by blinking. The addition of any tested concentration of TiO2QDs/BMI.BF4 powder provided immediate and long-term antibacterial activity without cytotoxic effect against the pulp fibroblasts. Furthermore, compared with Gctrl, G2.5% showed reliable polymerization behavior and degree of conversion without differences for softening in solvent with maintenance of bond adhesion to tooth immediately and over time. Thus, the incorporation of 2.5 wt% of TiO2QDs/BMI.BF4 in adhesive resin showed reliable physical, chemical, and biological properties.